A novel antimicrobial peptide against dental-caries-associated bacteria. (October 2017) - Chen, Long; Jia, Lili; Zhang, Qiang; Zhou, Xirui; Liu, Zhuqing; Li, Bingjie; Zhu, Zhentai; Wang, Fenwei; Yu, Changyuan; Zhang, Qian; Chen, Feng; Luo, Shi-Zhong
Abstract: Dental caries, a highly prevalent oral disease, is primarily caused by pathogenic bacteria infection, and most of them are anaerobic. Herein, we investigated the activity of a designed antimicrobial peptide ZXR-2, and found it showed broad-spectrum activity against a variety of Gram-positive and Gram-negative oral bacteria, particularly the caries-related taxa Streptococcus mutans . Time-course killing assays indicated that ZXR-2 killed most bacterial cells within 5 min at 4 × MIC. The mechanism of ZXR-2 involved disruption of cell membranes, as observed by scanning electron microscopy. Moreover, ZXR-2 inhibited the formation of S. mutans biofilm, but showed limited hemolytic effect. Based on its potent antimicrobial activity, rapid killing, and inhibition of S. mutans biofilm formation, ZXR-2 represents a potential therapeutic for the prevention and treatment of dental caries. Highlights: The activity of AMP ZXR-2 against oral facultative anaerobic bacteria was tested. ZXR-2 showed fast-killing activity and limited hemolytic activity. ZXR-2 prevented the formation of S. mutans biofilms.